Experimental study on bubble departure characteristics in subcooled nucleate pool boiling. (March 2017) - Goel, Parul; Nayak, Arun K.; Kulkarni, Parimal P.; Joshi, Jyeshtharaj B.
Highlights: Experiments of subcooled nucleate pool boiling. Observation of vapor bubble departure diameter (D) and frequency (f) under subcooled conditions. Parametric study of D and f with wall superheat and liquid subcooling. Parametric study of D and f with heater geometry, surface roughness and inclination angle. Abstract: The boiling models use departure diameter and frequency in closure relations for the calculation of nucleate boiling heat flux. These parameters are normally derived from empirical correlations which depend heavily on experiments. While these parameters are studied mostly for saturated conditions, there is not sufficient data for the values of departure diameter and frequency in subcooled boiling. In this work, the bubble departure characteristics, i.e. the departure diameters and frequency have been measured using high speed visualization experiments with subcooled demineralized water at atmospheric pressure for nucleate pool boiling conditions. The water pool dimensions were 300 mm × 135 mm × 250 mm with four different heating elements to carry out the parametric studies of bubble departure behavior. The considered parameters were heater surface roughness, heater geometry and heater inclination along with the experimental conditions like degree of subcooling (Δ Tsub = 5−20 K), superheat (Δ Tsat = 1−10 K) and the heat flux. The departure diameters and frequencies were directly measured from the images captured. It was intended to generate the subcooled nucleate pool boiling data under a wide range of conditions which are not present in the literature. The departure diameter was found to increase with the wall superheat, heater size and the inclination angle while the liquid subcooling and surface roughness produced a damping effect on the diameter. The departure frequency was found to increase with the wall superheat and the inclination angle, but decreases with an increase in the heater size. The frequency increases with the degree of subcooling except very close to the saturation, and is unaffected by the surface roughness beyond a certain superheat value.